Tasawuf: Jalan Menuju Pencerahan Batin Dan Pembebasan Sosial Dalam Moralitas Islam (Tazakka: Jurnal Pendidikan dan Keislaman, 2025)
This paper discusses Sufism as an ethic of liberation and its position in shaping Islamic morality. This study is motivated by concerns over spiritual decline and social inequality that are increasingly evident in the modern era.  This study uses a literature review method with a descriptive-qualitative approach. The analysis was conducted using a narrative review method to examine the concept of Sufism and its relevance to morality. We collected data from various literature related to Sufism and morality. The data were analyzed qualitatively to identify and interpret the relationship between Sufism teachings and the formation of morality. The results show that Sufism focuses on cleansing oneself of negative traits, such as greed and egoism, in order to achieve closeness to God. The history of Sufism dates back to the time of Prophet Muhammad through the practice of tahannuts and khalwat. In the present context, Sufism does not mean leaving the world, but rather transforming this mortal life into a means of divine devotion, so that the worldly dimension gains eternal value.
Keywords: Morality; Tasawuf; Inner; Social; Enlightenment; Religion